2011
DOI: 10.1093/gbe/evr015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Transposable Element Environment of Human Genes on Gene Length and Expression

Abstract: Independent lines of investigation have documented effects of both transposable elements (TEs) and gene length (GL) on gene expression. However, TE gene fractions are highly correlated with GL, suggesting that they cannot be considered independently. We evaluated the TE environment of human genes and GL jointly in an attempt to tease apart their relative effects. TE gene fractions and GL were compared with the overall level of gene expression and the breadth of expression across tissues. GL is strongly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…Their lengths are found to follow power-laws (Cohen et al, 2005;Costantini et al, 2006). See also (Jjingo et al, 2011) for other forms of participation of the different TE classes to the overall genomic architecture. All the above mentioned forms of genomic complexity undoubtedly contribute to the observed differences in the power-law features among organisms or TE classes, which are only partially explained by the use of our simple insertionelimination model.…”
Section: Discussionmentioning
confidence: 88%
“…Their lengths are found to follow power-laws (Cohen et al, 2005;Costantini et al, 2006). See also (Jjingo et al, 2011) for other forms of participation of the different TE classes to the overall genomic architecture. All the above mentioned forms of genomic complexity undoubtedly contribute to the observed differences in the power-law features among organisms or TE classes, which are only partially explained by the use of our simple insertionelimination model.…”
Section: Discussionmentioning
confidence: 88%
“…In one such study [8], our group identified MIRs to be the only TE-derived sequences whose presence shows a positive correlation to tissue-specific gene expression. Here, we provide evidence that this correlation is likely to be due to the propensity of MIRs to be exapted as enhancers that regulate cell-type and developmental-stage specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, a number of noncoding MIR sequences were found to be highly conserved, indicative of some functional, presumably regulatory, role (24). Later, it was shown that MIRs are enriched for open chromatin sites (25), encode regulatory RNAs (26), host gene promoters (27) and enhancers (28), and are also associated with tissue-specific expressed genes (29). Finally, and most importantly, MIRs are tRNA-derived SINEs (30) and their sequences include recognizable regulatory motifs, such as the promoter B-box element for Pol III binding, which are thought to be important for insulator activity.…”
Section: Significancementioning
confidence: 99%